Proteasome localization and activity in pig brain and in vivo small molecule screening for activators - Amrein Almira, Adriana; Chen, May W.; El Demerdash, Nagat; Javdan, Cameron; Park, Dongseok; Lee, Jennifer K.; Martin, Lee J. (Frontiers in Cellular Neuroscience, 2024)
Introduction Loss of proteasome function, proteinopathy, and proteotoxicity may cause neurodegeneration across the human lifespan in several forms of brain injury and disease. Drugs that activate brain proteasomes in vivo could thus have a broad therapeutic impact in neurology. Methods Using pigs, a clinically relevant large animal with a functionally compartmental gyrencephalic cerebral cortex, we evaluated the localization and biochemical activity of brain proteasomes and tested the ability of small molecules to activate brain proteasomes. Results By Western blotting, proteasome protein subunit PSMB5 and PSMA3 levels were similar in different pig brain regions. Immunohistochemistry for PSMB5 showed localization in the cytoplasm (diffuse and particulate) and nucleus (cytoplasm < nucleus). Some PSMB5 immunoreactivity was colocalized with mitochondrial (voltage-gated anion channel and cyclophilin D) and cell death (Aven) proteins in the neuronal soma and neuropil in the neocortex of pig and human brains. In the nucleus, PSMB5 immunoreactivity was diffuse, particulate, and clustered, including perinucleolar decorations. By fluorogenic assay, proteasome chymotrypsin-like activities (CTL) in crude tissue soluble fractions were generally similar within eight different pig brain regions. Proteasome CTL activity in the hippocampus was correlated with activity in nasal mucosa biopsies. In pilot analyses of subcellular fractions of pig cerebral cortex, proteasome CTL activity was highest in the cytosol and then ~50% lower in nuclear fractions; ~15–20% of total CTL activity was in pure mitochondrial fractions. With in-gel activity assay, 26S-singly and -doubly capped proteasomes were the dominant forms in the pig cerebral cortex. With a novel in situ histochemical activity assay, MG132-inhibitable proteasome CTL activity was localized to the neuropil, as a mosaic, and to cell bodies, nuclei, and centrosome-like perinuclear satellites. In piglets treated intravenously with pyrazolone derivative and chlorpromazine over 24 h, brain proteasome CTL activity was modestly increased. Discussion This study shows that the proteasome in the pig brain has relative regional uniformity, prominent nuclear and perinuclear presence with catalytic activity, a mitochondrial association with activity, 26S-single cap dominance, and indications from small molecule systemic administration of pyrazolone derivative and chlorpromazine that brain proteasome function appears safely activable.